Penilaian Fasilitas Pejalan Kaki Berdasarkan Persepsi Pengguna dan Pedestrian Level of Service (PLOS) - Hariani, Mira Lestira; Mahardiani, Gita (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2024)
Pedestrian facilities are a crucial element in sustainable urban planning to enhance safety, comfort, and accessibility for road users. This study aims to evaluate the quality of pedestrian facilities in the Perjuangan Street corridor, Cirebon City, which is designated as an educational area, using the Customer Satisfaction Index (CSI) and Pedestrian Level of Service (PLOS) approaches. The methods employed include pedestrian surveys, user satisfaction questionnaires, and an analysis of sidewalk geometric conditions based on the 2017 technical planning guidelines. The results indicate that pedestrian satisfaction with the available facilities falls within the